2008
DOI: 10.1254/jphs.fp0071738
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and Hepatoprotective Effects of Gomisin A on Fulminant Hepatic Failure Induced by D-Galactosamine and Lipopolysaccharide in Mice

Abstract: Abstract. This study examined the effects of gomisin A, a lignan compound from Schisandra fructus, on D-galactosamine (GalN) and lipopolysaccharide (LPS)-induced hepatic apoptosis and liver failure. Mice were given an intraperitoneal injection of GalN (700 mg /kg) / LPS (10 µg/ kg). Gomisin A (25, 50, 100, and 200 mg / kg) was administered intraperitoneally 1 h before the GalN / LPS injection. The liver injury was assessed biochemically and histologically. GalN/ LPS increased the serum aminotransferase levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…The condensation of Kupffer cells can be seen in C. myrrha pretreated (250 and 500 mg/kg; p.o.) rats may be due to apoptosis (Kim et al, 2008). There was a marked attenuation of these inflammatory alterations in a dosedependent manner in C. myrrha pretreated rat.…”
Section: Discussionmentioning
confidence: 80%
“…The condensation of Kupffer cells can be seen in C. myrrha pretreated (250 and 500 mg/kg; p.o.) rats may be due to apoptosis (Kim et al, 2008). There was a marked attenuation of these inflammatory alterations in a dosedependent manner in C. myrrha pretreated rat.…”
Section: Discussionmentioning
confidence: 80%
“…[11][12][13][14][15] In addition, hepatoprotective activities of S. chinensis have also been reported. [16][17][18][19] A recent study of ours showed that S. chinensis has a protective effect against ER stress-induced hepatic steatosis (unpublished data). S. chinensis contains various bioactive constituents, including lignans, triterpenoids, polysaccharides, and sterols.…”
mentioning
confidence: 66%
“…Several studies have demonstrated the diverse pharmacological activities of S. chinensis, which include anti-oxidant, anti-tumor, anti-obesity, anti-inflammatory, and cardioprotective effects [4-6, 15, 19]. In addition, hepatoprotective activities of S. chinensis have also been reported [8,9,14,25]. S. chinensis contains various bioactive constituents, including lignans, triterpenoids, polysaccharides, and sterols [10].…”
Section: Introductionmentioning
confidence: 99%